(untitled) (American International Journal of Economics and Finance Research, 2019)
Financially unsophisticated investors who consistently make sub-optimal financial decisions may suffer lasting consequences for long-term wealth accumulation and welfare. This study examines moderating effect of risk perception on financial knowledge, literacy and investment decision. Data was collected from 378 investors through the aids of structured questionnaires. The research hypotheses were tested using partial Least-square (PLS) regression. The findings reveals that there is positive and significant effect between financial knowledge, risk perception and investment decisions, while positive but insignificant effect was found between financial literacy and investment decisions. However, risk perception moderates the effect of financial literacy, investment knowledge on investment decisions. It recommends that investors, policymakers and individuals investors should embark on various educational programmes, to further influence the level of their investment decisions before committing their hard earning fund into project.